1989
DOI: 10.1200/jco.1989.7.5.662
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of intraarterial iododeoxyuridine in patients with colorectal liver metastases.

Abstract: Regional delivery of iododeoxyuridine (IdUrd) to patients with colorectal liver metastases was examined in a phase I study. The maximum-tolerated intraarterial (IA) dose (MTD) was 1,333 mg/m2/d administered continuously for 14 days. The dose-limiting toxicity was thrombocytopenia. Thrombocytopenia and leukopenia were correlated with the amount of IdUrd incorporated into DNA of peripheral granulocytes. In contrast to our experience with 5-fluorodeoxyuridine, there was no evidence of hepatobiliary toxicity. In 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…(2). In 4 of 9 patients treated with intrahepatic arterial infusions of IdUrd, Cheng et al reported tumor shrinkage to be between 40 to 65% (13). Morgan et al reported disappearance of ascites in patients with ovarian cancer treated with intraperitoneal IdUrd (12).…”
Section: Discussionmentioning
confidence: 99%
“…(2). In 4 of 9 patients treated with intrahepatic arterial infusions of IdUrd, Cheng et al reported tumor shrinkage to be between 40 to 65% (13). Morgan et al reported disappearance of ascites in patients with ovarian cancer treated with intraperitoneal IdUrd (12).…”
Section: Discussionmentioning
confidence: 99%
“…No peak was observed at the origin, which may come from incompletely digested DNA fragments. In Table 1, the values of base compositions are compared with those reported by others (Hurst, Marko & Butler 1953, Harold & Ziporin 1958, Burton 1960, Rudner, Shapiro & Chargaff 1966, Fasman 1976. Overall, a reasonable agreement with other data in both calf thymus and E. coli DNA is observed.…”
Section: Resultsmentioning
confidence: 99%
“…IUdR is a halogenated thymidine analogue and can be incorporated into DNA, replacing thymidine. IUdR has been recognized as an effective in vitro/in vivo radiosensitizer since the 1960s (7)(8)(9)(10)(11)(12)(13)(14); however, its clinical use is limited by a narrow therapeutic window when the drug is given as a continuous infusion (2). We have previously shown that oral IPdR treatment can improve the therapeutic index in comparison with continuous infusion IUdR by using an athymic nude mice model with several different human tumor xenografts (1).…”
Section: Introductionmentioning
confidence: 99%